2011
DOI: 10.1103/physrevc.83.054611
|View full text |Cite
|
Sign up to set email alerts
|

Role of angular momentum in the production of complex fragments in fusion and quasifission reactions

Abstract: The influence of angular momentum on the competition between complete fusion followed by the decay of compound nucleus and quasifission channels is treated within the dinuclear system model. The charge distributions of the products in the reactions 28 Si+ 96 Zr, 4 He+ 130 Te, and 40 Ca+ 82 Kr are predicted at bombarding energies above the Coulomb barrier. The results of calculations for the reactions 93 Nb+

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…It is known that the shell and pairing effects play a key role for the fission and quasi-fission process. It is found that the quasi-fission mass distribution in fusion reactions leading to the synthesis of super-heavy nuclei can be reasonably well described by the driving potential in the dinuclear system (DNS) model [17,18], since the shell effects of reaction system are effectively involved in the driving potential via the Q-value of the system. It is therefore interesting to investigate the mass distribution of a fissile system based on its driving potential.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the shell and pairing effects play a key role for the fission and quasi-fission process. It is found that the quasi-fission mass distribution in fusion reactions leading to the synthesis of super-heavy nuclei can be reasonably well described by the driving potential in the dinuclear system (DNS) model [17,18], since the shell effects of reaction system are effectively involved in the driving potential via the Q-value of the system. It is therefore interesting to investigate the mass distribution of a fissile system based on its driving potential.…”
Section: Introductionmentioning
confidence: 99%
“…At high angular momenta some dinuclear scission configurations are energetically more favorable than the compound nucleus configuration and the fissionlike fragments in the 36 Ar(E c.m. = 152 to 200 MeV) + 144 Sm reaction can be mainly produced by quasifission (but not by a fusion-fission process) [9]. The improved scission-point model [4,8] provides a good description of the experimental data on fission of 180 Hg as well as of 198 Hg (see [4]).…”
mentioning
confidence: 99%
“…The fission observables could be studied fully stochastically or using the thermodynamic properties. The dinuclear system model based on the thermodynamics with Boltzmann factor included [32][33][34][35] allows to calculate cross-section of fusion, fission and also evaporation or quasi-fission. The potential energy surface is obtained with two-center shell model (TCSM) and the emission barriers for particles, clusters is obtained with Skyrme-type nucleon-nucleon interaction.…”
Section: Introductionmentioning
confidence: 99%